INTERPERSONAL COMMUNICATION PATTERNS OF COACHES AND PLAYERS IN THE FUTSAL COMMUNITY TRAINING PROGRAM IN CENTRAL JAVA - Mauludin, Mohamad Alvian; Adiprabowo, Vani Dias (Universitas Teuku Umar, 2024)
This study aims to understand interpersonal communication patterns between coaches and players in futsal training programs within the FUTSAL BERSINAR community, while also identifying the supporting and inhibiting factors of such communication. Using a descriptive qualitative approach, data were collected through interviews and observations of both coaches and players, with analysis conducted through a case study paradigm. The data were analyzed using thematic analysis, which revealed that two-way communication was the most effective pattern in this context. This effectiveness was demonstrated by the coaches’ ability to deliver training material clearly and the players’ ability to provide feedback, which enhanced understanding and motivation. Furthermore, the study found that two-way communication contributed to the development of stronger relationships of trust between coaches and players. These findings confirm the critical role of effective communication in achieving optimal training results and fostering a supportive environment in futsal communities like FUTSAL BERSINAR.